PERCEIVED ORGANIZATIONAL SUPPORT SEBAGAI PEMEDIASI PENGARUH MOTIVASI INTRINSIK DAN EKSTRINSIK TERHADAP KINERJA BAGI PARATUR SIPIL NEGARA (ASN) PADA BKPSDMD KABUPATEN BUNGO - Nastavira Izmi, Inggrid; Hidayah, Zainur; Octavia, Ade (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
The aim of this research is to examine how Perceived Organizational Support functions as an intermediary factor linking both intrinsic and extrinsic motivation to the job performance of Civil Servants (ASN) at the Regional Civil Service and Human Resource Development Agency (BKPSDMD) in Bungo Regency. Motivation stands as a crucial driver behind employee productivity, as numerous studies have highlighted. Even employees with strong capabilities cannot reach their full potential without motivation. The research questions addressed include: (1) Does Intrinsic Motivation influence Perceived Organizational Support? (2) Does Extrinsic Motivation impact Perceived Organizational Support? (3) Is there a connection between Intrinsic Motivation and Performance? (4) Does Extrinsic Motivation affect Performance? (5) What effect does Perceived Organizational Support have on Performance? Employing a quantitative method, the study sampled all 37 employees within BKPSDMD Bungo Regency. Findings reveal that: (1) Intrinsic Motivation (X1) does not significantly affect Perceived Organizational Support (Y) (hypothesis not supported), (2) Extrinsic Motivation (X2) significantly impacts Perceived Organizational Support (Y) (hypothesis supported), (3) Intrinsic Motivation (X1) significantly influences Performance (Z) (hypothesis supported), (4) Extrinsic Motivation (X2) significantly affects Performance (Z) (hypothesis supported), and (5) Perceived Organizational Support (Y) significantly impacts Performance (Z) (hypothesis supported). This research aims to offer insight into how leadership and peer backing can bolster the connection between intrinsic motivation and the perception of organizational support